Raising the bar (13). Issue 4 (2nd October 2019) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Chasco, Coro; Corrado, Luisa; Doran, Justin; Felsenstein, Daniel; Fuerst, Franz; Le Gallo, Julie; McCann, Philip; Monastiriotis, Vassilis; et al.
ABSTRACT: This editorial summarises the papers published in issue 14(4) so as to raise the bar in applied spatial economic research and highlight new trends. The first paper analyses the impact of re-exports on bilateral trade data. The second paper proposes a new measure for the popular smart specialisation index (S3). The third paper proposes a new solution for the so-called reflection problem in spatial or social interaction models. The fourth paper analyses bankruptcy spillovers in the state of Maryland. The final paper estimates a system of equations to analyse the mutual relationship between the domestic migration of highly-skilled graduates and innovation and productivity in U.S. states.